PENGARUH KUALITAS SUMBER DAYA INSANI, KUALITAS PELAYANAN PETUGAS PEMADAM KEBAKARAN DAN FASILITAS TERHADAP KEPUASAN MASYARAKAT KABUPATEN TANAH DATAR - Elsha Afrida Puja Opjame; Zainuddin Zainuddin; Elsandra Eka Putra (IAIN Batusangkar, 2021)
The quality of public services is a major indicator of good governance, from the central government to local governments. Services provided by local governments such as the Tanah Datar Regency Fire Department. The main problem in this study is the indicator of community satisfaction in Tanah Datar Regency with the services provided by firefighters. This study uses a quantitative approach which is a method to test several theories by examining the relationship between variables with a sample of 88 respondents. Sampling using random sampling technique. The data analysis technique used multiple regression analysis, validity test, reliability test, uii t, f test, and classical assumption test. The results showed that the quality of human resources had a significant effect on community satisfaction, the quality of fire fighting services showed a significant effect on community satisfaction and facilities had a significant effect on community satisfaction. The quality of human resources, the quality of fire fighting services and facilities have a simultaneous effect on the satisfaction of the people of Tanah Datar Regency